CAMP: Congestion Avoidance and Mitigation Protocol for Wireless Body Area Networks - Anwar, Muhammad; Abdullah, Abdul Hanan; Saedudin, Rd. Rohmat; Masud, Farhan; Ullah, Fasee (International Journal of Integrated Engineering, 2018)
Advances in wireless communication technologies invented body sensor networks (BSNs) for health care systems. BSN monitor’s patients’ health remotely and automatically. It is economical and helpful solution for both patients and healthcare providers. WSN is made up of small Bio-medical sensors (BMSs) and Body Coordinator (BC). BMSs sense and transmit data continuously. As BSN consist of many BMSs, the simultaneous data transmission results in congestion in the network. Congestion causes packet drops which attempt to be retransmitted. In this work, we propose Routing scheme with Traffic Redirection and Rate Control (R-TRRC) for congestion detection and mitigation for BSNs. The experimental results shows that the propsed scheme carries out better results in terms of energy efficiency and network lifetime of BSNs.